Influence of Bimoment Restraints on the Load-Bearing Capacity of a Steel I-Beam - Wierzbicki, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study presents an analysis of steel I-beam warping. The calculations were made for hot-rolled IPE200 hinged beams with different lengths. After determining load-bearing capacity using the GMNIA method, the beams were strengthened with bimoment restraints at each end. The changes in critical moment and load-bearing capacity were then evaluated.
Keywords: steel beam; load capacity; warping; imperfections; stiffeners; bending; lateral-torsional buckling; GMNIA; belka stalowa; nośność; niedoskonałość; usztywnienie